Alkylated phase change composites for thermal energy storage based on surface-modified silica aerogels. Issue 5 (9th January 2015) - Huang, Xinyu; Liu, Zhenpu; Xia, Wei; Zou, Ruqiang; Han, Ray P. S.
Abstract : We alkylated silica aerogels to make them hydrophobic for effective impregnation and storage of a phase change material (PCM). Abstract : We alkylated silica aerogels to make them hydrophobic for effective impregnation and storage of a phase change material (PCM). As a result of this surface modification treatment, the aerogel scaffold exhibited an average increase of 20.9–34.7% in the PCM uptake with an improved thermal energy storage capacity and stability. For the light to thermal energy conversion experiments, we carbonized the treated aerogels and observed that they readily attained temperatures above the melting point of the PCM. Therefore, the carbonized PCM-impregnated scaffold possesses enhanced thermal energy storage and release property via a phase change response in the encapsulated PCM.